1933
DOI: 10.1021/j150349a004
|View full text |Cite
|
Sign up to set email alerts
|

The Absorption Spectra of a Series of Organic Molecular Compounds.

Abstract: Pfeiffer (1) and others have investigated the colored molecular compounds resulting from quiñones with aromatic hydrocarbons, ethers, or amines. Pfeiffer has classified these compounds with the quinhydrones and has shown that a series extends from the intensely colored quinhydrones existing as crystalline compounds, through colored complexes difficult to crystallize, to complexes impossible to crystallize and identified largely by a slight color change on mixing the liquid components. These latter "molecular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1954
1954
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Many of these unstable complexes display no visible absorption but rather have been recognized through the appearance of bands in the ultraviolet or infrared spectra of solutions of two components which are not characteristic of the parent compounds. Hunter and Northey (149) were perhaps the first investigators to report measurements outside the visible region in the detection of complex formation. They observed that the ultraviolet spectra of thin films of solutions of quiñones in various simple benzene derivatives were shifted toward the visible as compared to the spectra of the fused quiñones.…”
Section: E Spedrophotometric Measurementsmentioning
confidence: 99%
“…Many of these unstable complexes display no visible absorption but rather have been recognized through the appearance of bands in the ultraviolet or infrared spectra of solutions of two components which are not characteristic of the parent compounds. Hunter and Northey (149) were perhaps the first investigators to report measurements outside the visible region in the detection of complex formation. They observed that the ultraviolet spectra of thin films of solutions of quiñones in various simple benzene derivatives were shifted toward the visible as compared to the spectra of the fused quiñones.…”
Section: E Spedrophotometric Measurementsmentioning
confidence: 99%
“…This could be due to factors affecting heats of fusion as mentioned previously or it could indicate a special effect of alkyl substitution on the quinone ring. In solution studies, alkyl substitution of the quinone ring has been reported to decrease the equilibrium constant for addition compound formation between oxygenated aromatics and quiñones (5).…”
Section: Discussionmentioning
confidence: 99%